A review of pressure manipulating structure and performance in thermoelectrics. (4th May 2023) - Zhang, He; Zhang, Cunyin; Gregory, Duncan H; Yin, Zhanxiang; Wang, Yaqiang; He, Pan; Guo, Xin
Abstract: Pressure is a fundamental thermodynamic variable that can create exotic materials and modulate transport properties, motivating prosperous progress in multiple fields. As for inorganic thermoelectric materials, pressure is an indispensable condition during the preparation process, which is employed to compress raw powders into the specific shape of solid-state materials for performing properties characterization. In addition to this function, the extra influence of pressure on thermoelectric performance is frequently underestimated and even overlooked. In this review, we summarize recent progress and achievements of pressure-induced structure and performance in thermoelectrics, emphatically involving the modulation of pressure on crystal structure, electrical transport properties, microstructure, and thermal conductivity. According to various studies, the modulated mechanism of pressure on these items above has been discussed in detail, and the perspectives and strategies have been proposed with respect to applying pressure to improve thermoelectric performance. Overall, the purpose of the review is supposed to enrich the understanding of the mechanisms in pressure-induced transport properties and provide a guidance to rationally design a structural pattern to improve thermoelectric performance.